The Impact of Information Sharing on Supply Chain Performance through Supplier Quality Management, Supply Chain Agility, and Supply Chain Innovation - Harry Setyawan Firmansyah; Hotlan Siagian (Master of Management, School of Business and Management, Petra Christian University, 2022)
The study investigated the impact of information sharing on supply chain performance through supplier quality management, supply chain agility, and supply chain innovation. The data collection used a questionnaire designed with a 7-point Likert scale in GoogleForm and printed format and distributed through social media, email, WhatsApp, and mail posts. Of the 266 population, as many as 112 responses were received and were considered valid for further processing. The data analysis used the partial least square technique (PLS) utilizing SmartPLS. The analysis showed that information sharing directly affects supplier quality management, supply chain agility, and supply chain innovation. Furthermore, supply chain agility, supplier quality management, and supply chain innovation directly affect operational performance. The exciting result of this study is the indirect effect of information sharing on operational performance through the mediating role of supply chain agility, supplier quality management, and supply chain innovation. This result offers solutions to practitioners to pursue information sharing, supplier quality management, supply chain agility, and supply chain innovation in improving operational performance. The main theoretical contribution of this research is the mediating role of supply chain agility, supply chain innovation, and supplier quality management toward the relationship between information sharing and operational performance.